Diagnosis and management of symptoms associated with vulvovaginal atrophy: expert opinion on behalf of the Italian VVA study group (*) - Nappi, Rossella E. (Taylor & Francis, 2016)

(untitled) (Gynecol Endocrinol)
Vulvovaginal atrophy (VVA) is a chronic disorder that commonly occurs in postmenopausal women, whose symptoms are recognized among the most frequent and bothersome symptoms associated with menopause. The principal therapeutic goal in managing VVA is to relieve symptoms as well as to restore the vaginal environment to a healthy state. However, despite its high prevalence and negative impact on quality of life, VVA is underreported by women, underrecognized by gynecologists, and therefore, undertreated. In the light of the new development of treatment options for VVA, we here provide an updated expert opinion on the management of VVA. In particular, we strongly recommend that HCPs proactively start an open discussion with their postmenopausal patients about urogenital symptoms. Treatment should be started as early as the first symptoms of VVA occur and should be maintained over time, due to the chronicity of the conditions. Many treatment options are now available and therapy should be individualized, taking the woman’s preference in consideration.